2018
DOI: 10.1016/j.otsr.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of operative time on early joint infection and deep vein thrombosis in primary total hip arthroplasty

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…Previously it has been proved that increased operative time could result in higher complication rate especially infection, venous thromboembolism (VTE) and patient dissatisfaction (24,(26)(27)(28)(29)(30)(31). Each TKA surgery in this study took an average of 60.30 minutes (SD = 44.19) from incision to wound dressing, which is comparable to other reports (27,32).…”
Section: Characteristicssupporting
confidence: 76%
“…Previously it has been proved that increased operative time could result in higher complication rate especially infection, venous thromboembolism (VTE) and patient dissatisfaction (24,(26)(27)(28)(29)(30)(31). Each TKA surgery in this study took an average of 60.30 minutes (SD = 44.19) from incision to wound dressing, which is comparable to other reports (27,32).…”
Section: Characteristicssupporting
confidence: 76%
“…41 The other previous studies also indicated that prolonged operative time are associated with increased rates of postoperative complications, such as the surgical site infection and delayed wound healing. [42][43][44] In the current study, our results showed that IF has a less operative time than AR. Although Park et al reported that the operative time of IF group is similar with that of AR group, 31 the other 10 included studies reported the similar result with that of meta-analysis.…”
Section: Operative Time Blood Loss and Transfusionsupporting
confidence: 56%
“…Operative times have historically been identified as an important factor in postoperative outcomes for TKA. Increasing operative times are associated with worse outcomes, such as increased rates of infections, thromboemboli, neurologic deficits, revisions, and other complications (3)(4)(5)(6)(7)(8)(9)(10). Young et al analyzed 61,438 TKAs in the New Zealand Joint Registry over a 13-year period and found increasing revision rates with operative times longer than 120 minutes (P<0.01) (10).…”
Section: Introductionmentioning
confidence: 99%